Lymphocyte and CD62E expression in lichen planus and lichenoid reaction - Juliana Tristão Werneck; Lúcio Souza Gonçalves; Letícia Côgo Marques; Arley Silva Junior (BMC, 2022)
Abstract Background It is difficult to distinguish the clinical and histopathological aspects of oral lichen planus lesions from those of oral lichenoid reaction. Some criteria were proposed to distinguish them, mainly because they have different biological behaviors. The aim of the present study was to compare the lymphocyte population and the expression of E-selectin between these lesions. Methods Participants with a clinical diagnosis of oral lichen planus (GOLP) and oral lichenoid reaction (GOLR) who needed to perform a biopsy were selected. The tissue was frozen and immunostaining was performed for CD3/CD4, CD3/CD8, CD4/CLA, CD8/CLA, and CD62E. The analysis of each immunostaining was accomplished using the ImageJ program. Results In total, 25 participants with oral lichen planus and 11 with oral lichenoid reaction were seen. In the evaluation of CD3 + CD4+/CD3 + and CD3 + CD8+/CD3 + proportions, there was a higher percentage of these cells in the oral lichen planus group when compared with the oral lichenoid reaction group (p = 0.027 and p = 0.038 respectively). The average number of CLA + lymphocytes for CD4+/CLA + and CD8+/CLA + in both groups was not statistically significant (p = 0.840; d = 0.363). In GOLP, the number of CD4 + CLA+/E-selectin and CD8 + CLA+/E-selectin was not statistically significant (p = 0.951 and p = 0.454 respectively); neither in GOLR (p = 0.454 and p = 0.989 respectively). Conclusion Our results indicate that CD3 + CD4+, CD3 + CD8+, CD4 + CLA+, CD8 + CLA + lymphocytes and E-selectin are present in both lesions. However, the proportion of CD3 + CD4+/CD3 + and CD3 + CD8/CD3 + cells is higher in the oral lichen planus group when compared with the oral lichenoid reaction group, suggesting that these cells may be important for the etiopathogenic mechanism of these lesions.